Ø¹Ù†Ø§ÙŠØ© Ø§Ù„Ù…ØºØ§Ø±Ø¨Ø© Ø¨Ø§Ù„Ø³ÙŠØ±Ø© Ø§Ù„Ù†Ø¨ÙˆÙŠØ© (ÙƒØªØ§Ø¨ Ø§Ù„Ø´Ù…Ø§Ø¦Ù„ Ø£Ù†Ù…ÙˆØ°Ø¬Ù‹Ø§) - Murad Zahwi (Ø§Ù„Ø¨ØµÙŠØ±Ø©: Ù…Ø¬Ù„Ø© Ø§Ù„Ø¯Ø±Ø§Ø³Ø§Øª Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ©, 2022)
This study aims to find out how the Moroccan community pays attention to the sirah nabawiyyah, specifically in the book of al-SyamÄ'il al-Muá¸¥ammadiyyah. This study uses a qualitative method with a descriptive analytical and historical approach. The results showed that among the forms of Moroccan people's attention to the sirah of the Prophet Muhammad especially the book of al-SyamÄ'il al-Muá¸¥ammadiyyah is the number of syurÅ«á¸¥ (explanations) of the Moroccans to the book of al-SyamÄ'il al-Muá¸¥ammadiyyah as evidence of their attention to the book. The book of al-SyamÄ'il al-Muá¸¥ammadiyyah by al-TirmiÅ¼Ä« is one of the most important references to get to know the figure of the Prophet because it has contained everything related to his character, character and physical. Al-TirmiÅ¼Ä« strongly maintains the validity of the hadith and is committed to the validity of the hadith he narrates